HUBUNGAN PARITAS DAN USIA IBU DENGAN PENGETAHUAN IBU NIFAS TENTANG TANDA-TANDA BAHAYA NIFAS DI DESA CIJAGRA KECAMATAN PASEH KABUPATEN BANDUNG - Abdul Qudus; Yovi Regariana (Jurnal Infokes, 2020)
According to the World Healt Organization (WHO) directly related to the causes of maternal and infant mortality in the case in 2007, was 60% bleeding, poisoning toksemin gravidarum or pregnancy 20% and 20% infection, while the infant mortality due aspeksia 40 %, LBW and prematurity 25% and 35% infection.Objective, To determine the relationship of parity and maternal age at childbirth maternal knowledge about postpartum danger signs in the Village District Cijagra Paseh Bandung regency. The research method used in this study is the correlation, the study design was conducted with cross sectional approach, sampling was done by using total sampling instruments for data collection questionnaire.The research instrument used questionnaires in 30responden, Research data is processed quantitatively by univariate method, bivariate with logistic regression analysis of SPSS program. Based on the frequency distribution of the age of 30 nearly half of respondents (30.0%) were aged <20 years (43.3%) and aged between 20-35 years (26.7%) were aged> 35 years. Parity (50%) classified as primiparous (43.31%) and multiparous (6.7%) grande multipara. Knowledge (13.3%) either knowledgeable, (30.0%) and knowledgeable enough (56.7%) are less knowledgeable. The statistical result that the value of X2 show hit (22.647)> X2 Tab 5% (9.488) / or r = 0.000 <0.05 so it can be concluded that the relationship between the age of knowledge, based on Chi-square test showed a significant relationship.